Vacuum fluctuations in theories with deformed dispersion relations - Arzano,M; Gubitosi,G; Magueijo,J; Amelino-Camelia,G (Physical Review D, 2015)
We examine vacuum fluctuations in theories with modified dispersion relations which represent dimensional reduction at high energies. By changing units of energy and momentum we can obtain a description rendering the dispersion relations undeformed and transferring all the nontrivial effects to the integration measure in momentum space. Using this description we propose a general quantization procedure, which should be applicable whether or not the theory explicitly introduces a preferred frame. Based on this scheme we evaluate the power spectrum of quantum vacuum fluctuations. We find that in all theories which run to two dimensions in the ultraviolet the vacuum fluctuations, in the ultraviolet regime, are scale invariant. This is true in flat space but also for “inside the horizon” modes in an expanding universe. We spell out the conditions upon the gravity theory for this scale invariance to be preserved as the modes are frozen-in outside the horizon. We also digress on the meaning of dimensionality (in momentum and position space) and suggest that the spectral index could itself provide an operational definition of dimensionality.